Analysis of multi-source energy system for small-scale domestic applications. Integration of biodiesel, solar and wind energy. (February 2020) - Algieri, A.; Morrone, P.; Perrone, D.; Bova, S.; Castiglione, T.
Abstract: The paper aims at analysing the energy performance of an innovative multi-source energy system for residential small-scale combined heat and power (CHP) applications. The integrated system is based on an Organic Rankine Cycle (ORC) fuelled by biodiesel, a wind turbine, and a photovoltaic unit. The application refers to the Italian residential sector. The ORC system operates in order to satisfy the thermal demand of domestic users while wind and solar based sub-systems work in parallel to increase the electric self-consumption rate. An auxiliary boiler provides thermal energy when the CHP thermal output is low. Furthermore, when the solar and/or wind sources are significant, the ORC can be switched-off or operated at partial load. A preliminary investigation is performed to define the proper size of the ORC unit. Afterwards, the analysis is focused on a multi-variable optimisation of the integrated system. In particular, the nominal power of the wind turbine and photovoltaic units have been found in order to guarantee a proper trade-off between electric self-consumed and surplus energy.